Fine particulates over South Asia: Review and meta-analysis of PM2.5 source apportionment through receptor model. (April 2017) - Singh, Nandita; Murari, Vishnu; Kumar, Manish; Barman, S.C.; Banerjee, Tirthankar
Abstract: Fine particulates (PM2.5 ) constitute dominant proportion of airborne particulates and have been often associated with human health disorders, changes in regional climate, hydrological cycle and more recently to food security. Intrinsic properties of particulates are direct function of sources. This initiates the necessity of conducting a comprehensive review on PM2.5 sources over South Asia which in turn may be valuable to develop strategies for emission control. Particulate source apportionment (SA) through receptor models is one of the existing tool to quantify contribution of particulate sources. Review of 51 SA studies were performed of which 48 (94%) were appeared within a span of 2007–2016. Almost half of SA studies (55%) were found concentrated over few typical urban stations (Delhi, Dhaka, Mumbai, Agra and Lahore). Due to lack of local particulate source profile and emission inventory, positive matrix factorization and principal component analysis (62% of studies) were the primary choices, followed by chemical mass balance (CMB, 18%). Metallic species were most regularly used as source tracers while use of organic molecular markers and gas-to-particle conversion were minimum. Among all the SA sites, vehicular emissions (mean ± sd: 37 ± 20%) emerged as most dominating PM2.5 source followed by industrial emissions (23 ± 16%), secondary aerosols (22 ± 12%) and natural sources (20 ± 15%). Vehicular emissions (39 ± 24%) also identified as dominating source for highly polluted sites (PM2.5 >100 μgm -3, n = 15) while site specific influence of either or in combination of industrial, secondary aerosols and natural sources were recognized. Source specific trends were considerably varied in terms of region and seasonality. Both natural and industrial sources were most influential over Pakistan and Afghanistan while over Indo-Gangetic plain, vehicular, natural and industrial emissions appeared dominant. Influence of vehicular emission was found single dominating source over southern part while over Bangladesh, both vehicular, biomass burning and industrial sources were significant. Graphical abstract: Relative source contributions (in percentage) to PM2.5 over South Asia. Highlights: Geography and seasonality significantly influences PM2.5 source strength. Limited use of organic molecular marker and gas-to-particle conversion in PM2.5 SA. Vehicular emissions are most dominating followed by industries & secondary aerosol. Natural and industrial sources are mostly dominant over upper South Asia. Vehicular, industrial and biomass burning are main emitters over lower South Asia. Abstract : Heterogeneities of PM2.5 sources were reported throughout South Asia both in terms of seasons and geography with dominance of vehicular and industrial sources.